Pengaruh Konten Youtube #Logindiclosethedoor terhadap Sikap Toleransi Mahasiswa KPI UIN Jambi - Dita Nurul Fajrin; M. Junaidi Habe; Agus Salim; Abdul Kholiq Muhabasya; hafizen; Usrial; Andeka Widodo (Journal of Religion and Film, 2024)
This research is motivated by the urgency of tolerance in the digital era which should be mainstreamed in order to realize peaceful and harmonious coexistence amidst the diversity of Indonesian society. As is done on Deddy Corbuzier's YouTube channel which raises the theme of tolerance in religion and diversity. This theme certainly cannot be separated from the nuances of Ramadan, the content is named #LogIndiCloseTheDoor. From this problem, researchers identified two problems, namely: First, is there an influence of YouTube content #LogIndiCloseTheDoor on the tolerant attitude of Islamic Communication and Broadcasting students at Sulthan Thaha Saifuddin State Islamic University, Jambi. Second, whether Islamic Communication and Broadcasting students at Sulthan Thaha Saifuddin Jambi State Islamic University become more tolerant after watching YouTube content #LogIndiCloseTheDoor. The research approach that the author uses is quantitative correlational research methods using observation, questionnaires and documentation. A total of 52 respondents were selected as samples from a population of 159 students of the Islamic Communication and Broadcasting Study Program at UIN Jambi, from semester 8, in the 2023/2024 academic year. Data processing was carried out using SPSS statistical software by analyzing the 12 question items in the questionnaire to obtain more structured and informative results. The results of this research show that the YouTube content #LogIndiCloseTheDoor influences the tolerance attitude of Islamic Communication and Broadcasting students at Sulthan Thaha Saifuddin Jambi State Islamic University as proven by a simple linear regression test with the tolerance attitude variable that t count > t table, namely 6.487 is greater than 4.03 which means Ho is rejected and Ha is accepted. Thus, the results of this research are in accordance with the cultivation theory that mass media also maintains, disseminates and unifies the values ​​that exist in society. In this research, the content of #LogIndicloseTheDoor is considered capable of spreading the values ​​of tolerance to Islamic Communication and Broadcasting students at Sulthan Thaha Saifuddin Jambi State Islamic University so that students become more respectful of each other in everyday life